Therapeutic Potential of a New Jumbo Phage That Infects Vibrio coralliilyticus, a Widespread Coral Pathogen - Jacquemot, Loïc; Bettarel, Yvan; Monjol, Joanne; Corre, Erwan; Halary, Sébastien; Desnues, Christelle; Bouvier, Thierry; Ferrier-Pagès, Christine; Baudoux, Anne-Claire (Frontiers in Microbiology, 2018)
Biological control using bacteriophages is a promising approach for mitigating the devastating effects of coral diseases. Several phages that infect Vibrio coralliilyticus, a widespread coral pathogen, have been isolated, suggesting that this bacterium is rather permissive to viral infection and is, therefore, a suitable candidate for treatment by phage therapy. In this study, we combined functional and genomic approaches to evaluate the therapeutic potential of BONAISHI, a novel Vibrio V. coralliilyticus phage, which was isolated from the coral reef in Van Phong Bay (Vietnam). BONAISHI appears to be strictly lytic for several pathogenic strains of V. coralliilyticus and remains infectious over a broad range of environmental conditions. This candidate has an unusually large dsDNA genome (303 kb), with no genes that encode known toxins or implicated in lysogeny control. We identified several proteins involved in host lysis, which may offer an interesting alternative to the use of whole bacteriophages for controlling V. coralliilyticus. A preliminary therapy test showed that adding BONAISHI to an infected culture of Symbiodinium sp. cells reduced the impact of V. coralliilyticus on Symbiodinium sp. photosynthetic activity. This study showed that BONAISHI is able to mitigate V. coralliilyticus infections, making it a good candidate for phage therapy for coral disease.